Challenges and Prospects of Crypto-Currency Market Development - O. P. Kultygin; N. N. Lyublinskaya; E. N. Tokmakova; A. E. Trubin (Вестник Российского экономического университета имени Г. В. Плеханова)
The article deals with the research on global crypto-currency market and analysis of its development trends. Special attention was paid to national regulation of crypto-currency and activity connected with it, which is topical today due to introduction of new sanctions against Russia, including those in the field of crypto-exchanges. Through analyzing the development of finance blockchain-systems the authors identified the vector of their developing in the direction of raising the speed of work, upgrading algorithms of consensus, increasing security and control over the mining sphere and turnover of crypto-currency in Russia. A conclusion was drawn that it can foster the extended use of crypto-systems of distributed ledger by present day banks. As goals of the research the authors mentioned problems connected with the opportunity to use blockchain technologies in the credit and finance sector and forecasting effects of such use.